2016
DOI: 10.1002/dev.21444
|View full text |Cite
|
Sign up to set email alerts
|

Maternal separation increases later immobility during forced swim in guinea pig pups: evidence for sensitization of a depressive‐like state

Abstract: Early-life stress is thought to increase later vulnerability for developing depressive illness by sensitizing underlying stress-responsive systems. Guinea pig pups separated from their mother and isolated in a novel cage for 3 hr exhibit a sensitized depressive-like behavioral response when separated again the following day as well as weeks later. The behavioral response and its sensitization appear to be mediated by inflammatory factors. To determine if this sensitization is specific to the separation respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This result is in agreement with previous reports (Amini‐Khoei et al, 2017; Gracia‐Rubio et al, 2015). Similarly, many studies have observed depression‐like behaviours in MS offspring in models such as the forced swim test, tail suspension test, or splash test (Amini‐Khoei et al, 2017; Bian et al, 2015; Dimatelis et al, 2012b; Hennessy et al, 2016). Anxiety‐like symptoms were evaluated by the elevated plus maze test and social preference tests, and the results indicated that MS also increases anxiety levels in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with previous reports (Amini‐Khoei et al, 2017; Gracia‐Rubio et al, 2015). Similarly, many studies have observed depression‐like behaviours in MS offspring in models such as the forced swim test, tail suspension test, or splash test (Amini‐Khoei et al, 2017; Bian et al, 2015; Dimatelis et al, 2012b; Hennessy et al, 2016). Anxiety‐like symptoms were evaluated by the elevated plus maze test and social preference tests, and the results indicated that MS also increases anxiety levels in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings indicate that a several-hour period of separation of guinea pig pups from the attachment figure in a threatening (i.e., novel, brightly lit) environment evokes an inflammatory-mediated depressive-like response that sensitizes with repeated separation. The validity of this model for the study of depression is supported by the recent finding that an initial 3-hour separation also increased later depressive-like responding in the most widely used screen for antidepressant medication, i.e., previous separation increased immobility in the forced swim test (Hennessy et al, 2017).…”
Section: Introductionmentioning
confidence: 86%
“…Maternal separation (MS) in rodents, especially rats, has been widely used to elicit the effect of early life stress on mood disorders (Tractenberg et al, 2016;Vetulani, 2013). MS has been reported to increase anxiety and depressive behaviors and cause cognitive disorder in adulthood, which was accomplished by alterations in HPA axis, decreased BDNF expression and altered structural and functional plasticity in the medial prefrontal cortex and hippocampus in rats and mice (Hennessy, Schreibeis, Schiml, & Deak, 2017;Musazzi et al, 2009;Seo et al, 2017;Tractenberg et al, 2016;Vetulani, 2013; van Zyl, . Though most mental disorders in humans often begin to onset during adolescence (Kessler et al, 2007), previous studies in rodent models, however, mostly focused on the adult outcomes of early life stress (Schroeder, Notaras, Du, & Hill, 2018).…”
mentioning
confidence: 99%